DESIGN AND EVALUATION OF A MANAGEMENT FRAMEWORK FOR ONLINE VISUAL ART EDUCATION PLATFORMS - Dingankar, Shreyas; Dixit, Rajita; Tarnekar, Seema; Patil, Dr. Jayashree; Pujari, Ketaki Anay; Puntambekar, Devendra (ShodhKosh: Journal of Visual and Performing Arts, 2025)
During and after the COVID-19 pandemic, online visual art education has grown, but most platforms do not have adequate governance and operational infrastructure. The courses in art demand studio-like work, critique and handling of huge media files. The generic learning management systems are generally ineffective, as it prioritizes the text-based courses and fails to consider intellectual property or community safety. The given paper suggests a management system applicable to online platforms of visual art education. The framework was created based on the existing platforms analysis, stakeholder needs and gaps in literature analysis. It consists of governance systems, curriculum-level lifecycle management, studio orchestration, quality assurance, community moderation, learner support, analytics and privacy protection. A pilot study on a medium art website was analyzed in terms of user interaction and performance indicators. Quantitative findings indicate that course completion (71.2 to 83.6 percent), the number of learners who are active weekly, and the critique and system usability are improved, whereas feedback and support response time significantly drop. The qualitative feedback was marked with more distinct roles, faster moderation and increased learner satisfaction. The results imply that the quality of learning and operational efficiency of visual art platforms can be improved by organizing management processes. It has implications that guide administrators aiming to professionalize art-oriented platforms, and provide policy-makers with information about digital studio pedagogy. The adaptive analytics in creativity evaluation and cross-platform accreditation should be studied in the future.